Shaping the future : a long-term perspective of people and job mobility for the Middle East and North Africa (World Bank, 2009)
The objective of this study is to provide a long-term perspective for the ongoing policy dialogue on the management of labor migration in Europe and the Middle East and North Africa (MENA) countries. It is organized as follows. Chapter one puts the report and migration in the context of the economic and social development in MENA countries. Chapter two provides the historical context of MENA migration patterns and an overview of the presence and skill characteristics of migrants in Organization for Economic Co-operation and Development (OECD) countries today. This chapter also discusses the potential for insourcing, that is, migration of jobs into the region as an alternative or complement to labor migration. Chapter three analyzes the demand and supply framework for migration, the determinants of migration patterns, and the potential demand for labor in the European Union (EU), and the characteristics and trends of MENA labor supply. Chapter four looks to the worldwide impact of demographic and labor force developments in the decades ahead and their implications on labor and job mobility. The chapter analyzes the likely population and labor force growth in Europe and MENA, the challenges this growth poses, and the scope for demographic arbitrage between the two regions. This chapter provides the basis for the fifth and concluding chapter. Chapter five covers the institutional setup and the various economic and social protection policies and practices worldwide that have a strong and positive bearing on migration flows and presents a conceptual framework on both the labor and job sending and receiving sides that can be used by policy makers to articulate, defend, and implement a collaborative approach to the challenges ahead.